[Rezension von: Graulich, Markus, 1964-, Das neue kirchliche Strafrecht : Einführung und Kommentar] - Němec, Damián 1960-; Graulich, Markus 1964-; Hallermann, Heribert 1951- (2022)
The review presents a book by two experienced German authors, experts in the penal law of the Catholic Church, presenting in a concise and clear manner the new Book VI of the 1983 Code of Canon Law, promulgated in 2021 by Pope Francis' Apostolic Constitution Pascite gregem Dei, to users in the German-speaking area. The authors present the origins of the revised text, its main features, and provide commentary on each individual canon. They also present the original Latin texts and the German translation of both the Apostolic Constitution and the new Book VI of the Codex itself. Synopses of the original 1983 text and the revised 2021 text, in both Latin and German, also facilitate familiarity with the new legislation.
Keywords: Apostolic Constitution; Catholic Church; Code of Canon Law; Pope Francis; penal law; Rezension